Temperature Effects on the Plasmon Modes of Double-layer Graphene - Tuan, Dinh Van; Khanh, Nguyen Quoc (Communications in Physics, 2012)
We calculate the dynamical dielectric function of doped double-layer graphene (DLG), made of two parallel graphene monolayers with carrier densities \(n_1, n_2\), respectively, and a separation interlayer of \(d\) at finite temperature. The results are used to find the dispersion of plasmon modes. We study the temperature effects on the DLG plasmon modes in the case of symmetric system \((n_1=n_2)\), asymmetric system \((n_1 eq n_2)\) and no free carriers in the second layer \((n_2=0)\). We show that the effect of temperature on the plasmon dispersion is significant and can not be ignored in investigating graphene properties.